El material didáctico impreso y la influencia en el proceso de enseñanza aprendizaje en la unidad a distancia, centro de apoyo Riobamba, de la facultad de administración de empresas de la Escuela Superior Politécnica de Chimborazo (ESPOCh), período 2009-2010. Lineamientos alternativos - Molina Machado, Wilson Antonio (2011)
The research work is presented to the main aims to analyze the influence of printed materials in the teaching-learning process in the Distance Unit, Riobamba Support Center, Faculty of Business Administration from the Chimborazo Polytechnic School (ESPOCH), 2009-2010. For this purpose the theoretical field, the printed materials and teaching-learning process in distance education were investigated. In order to achieve this goal, information was collected using methods and techniques capable of achieving the development process of the investigation. In terms of methodology, we applied the methods: analytic, synthetic, inductive and deductive, which helped in the processing of empirical information, as well as for the analysis of cases to make comparisons and establish relationships that allow easily understand the origin of the problem, in the teaching-learning process of the Distance Unit, Support Center Riobamba, Faculty of Business Administration from the Chimborazo Polytechnic School (ESPOCH). They were also useful for summarizing and reconstruction of all elements and aspects of greater relevance, drawing up conclusions, verify and test hypotheses and to establish general criteria for the problems investigated. The techniques used as aids for data collection was the survey yielded information and an overview of the weaknesses of the Support Center with regard to the Preparation of printed materials. As a result of the investigation has yielded some results, which are listed below: It is noted that the structure of printed materials does not comply with the philosophy and requirements of students of distance education. The structure of printed materials does not promote adequate teacher-student relationship, because it does not contain information, activities, links and it does not motivate to investigate the subject. The rigor of the process for the development of print resources is ensuring that they meet the requirements of distance education. Many types of resources including printed materials, which are the curricula vehicles to achieve the objectives. Throughout the research process allowed reaching the findings, which show that the printed materials used in the Distance Unit, Riobamba Support Center, Faculty of Business Administration of ESPOCH, in 2009-2010, are made without a proactive guide that provides relevant content and designs, so have become known as something like the notes, and a collection of unstructured information, which has hindered the teaching-learning process in the Education Unit Distance.